2017
DOI: 10.15823/p.2017.47
|View full text |Cite
|
Sign up to set email alerts
|

Moodle as Virtual Learning Environment in Developing Language Skills, Fostering Metacognitive Awareness and Promoting Learner Autonomy

Abstract: The study evaluates the potentially relative effectiveness of Moodle as one of the virtual learning environments applied to develop English language skills, foster metacognitive awareness and promote learner autonomy in university settings. The respondents from Mykolas Romeris University and Lithuanian University of Educational Sciences were asked to express their attitude towards Moodle learning environment and assess their views on the improvement of language skills as well as fostering their metacognitive a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 7 publications
3
18
0
Order By: Relevance
“…There has been a growing demand for the integration of e-learning and e-teaching technology in teaching and learning foreign languages (Dayag, 2018;Fabbian, Carney, & Grgurovic, 2017;Gulbinskienė, Masoodi, & Šliogerienė, 2017;Maduabuchi, 2016;Pinto-Llorente, Sánchez-Gómez, García-Peñalvo, & Casillas-Martin, 2017;Saldaña, 2015). In this respect, Marzban (2010) proclaims that teachers at all levels of education increasingly need to integrate e-learning in their course delivery systems and their perceptions need to be assessed regularly to ascertain to the effectiveness of virtual education in learning and teaching foreign languages and to report on difficulties that potentially arise in such new environments.…”
Section: Review Of the Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…There has been a growing demand for the integration of e-learning and e-teaching technology in teaching and learning foreign languages (Dayag, 2018;Fabbian, Carney, & Grgurovic, 2017;Gulbinskienė, Masoodi, & Šliogerienė, 2017;Maduabuchi, 2016;Pinto-Llorente, Sánchez-Gómez, García-Peñalvo, & Casillas-Martin, 2017;Saldaña, 2015). In this respect, Marzban (2010) proclaims that teachers at all levels of education increasingly need to integrate e-learning in their course delivery systems and their perceptions need to be assessed regularly to ascertain to the effectiveness of virtual education in learning and teaching foreign languages and to report on difficulties that potentially arise in such new environments.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…As e-learning platforms and other assistive educational technology continue to expand and develop by leaps and bounds, higher education institutions race to adopt and adapt such technologies to harness them in the delivery and teaching of their courses online to help learners get connected, personalized and pro-learning styles, incentivized, and individualized approaches to learning and teaching (Bannister, 2016;Beard, 2017;Boulton, Kent, & Williams, 2018;Bower, Lee, & Dalgarno, 2017;Sorbie, 2015). Many a researcher observed that university faculty often find difficulty in finding sources of authentic speech, written or oral, produced by professional native speakers but over YouTube and the like (See for instance, Gulbinskienė, Masoodi, & Šliogerienė, 2017;Han & Ellis, 2019;Vo, Mozelius, Jaldemark, Håkansson, & Lindqvist, 2018;Weerasinghe, 2018;Vo, Zhu, & Diep, 2017;Zeichner & Zilka, 2016). Online apps like YouTube can even be mashed up in the tools of e-learning platforms such as Blackboard ® , thereby providing professional teaching materials or videos by expert native speakers.…”
Section: Introductionmentioning
confidence: 99%
“…Massive Open Online Courses (MOOCs) are expanding the scope of online distance learning. Some modern researchers focus on studies of self-regulated learning skills profiles among learners enrolled in a Modular Object-Oriented Dynamic Learning Environment (Moodle) online course [74][75][76][77]. The analysis shows that online self-regulation and computer self-efficacy influences grades in a positive way.…”
Section: Methodsmentioning
confidence: 99%
“…The interest to the concept of developing autonomy in foreign language learning through interaction has increased over the recent years due to the spread of virtual environment (Gulbinskiene et al, 2017) and blended learning environment (Hwang et al, 2009) in professional education. Still the research of the concept of autonomy, its efficiency and application in pedagogical education is insufficient.…”
Section: Review Of Literaturementioning
confidence: 99%